Pengaruh Layanan Digital, Aspek Permodalan, dan Growth Opportunity Terhadap Kinerja Keuangan Perbankan - Sherlina Nur Aprilia; Dewi Saptantinah Puji Astuti (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
This study aims to analyse the significance of digital services, capital structure and growth opportunities on the financial performance of banks. The population of interest in this study comprises digital banks registered with the Financial Services Authority (OJK) between 2021 and 2023. The sample comprises 12 banks, selected using a non-probability sampling technique and a purposive sampling method. This is a quantitative study, with secondary data sourced from financial and annual banking reports. Multiple linear regression analysis was performed using the IBM SPSS Statistics version 24 computer program. The results of this study indicate that digital services have no significant effect on the financial performance of banks, while capital aspect and growth opportunities have a negative and significant effect on the financial performance of banks.